E-learning Material on Gender Equality in Information System Professions - Brita Somerkoski; Reima Suomi (United States, 2022)
Gender equality is a worldwide actual issue touching upon every one of us. Without gender equality, we cannot reach a sustainable world. Information technology seems to be a domain and professional area where men have traditionally dominated, without any good reason. There is a worldwide call for more women to become IS professionals. In this article, we review what kind of open-access material to educate about gender equality in Information System domain and professions can be found. Together 6 (n=6) material sets were found, mainly targeted for adolescents. Public bodies such as UN or UNESCO provide open source materials, though activity of some private parties can also be found.
IC4E 2020: Proceedings of the 2020 11th International Conference on E-Education, E-Business, E-Management, and E-Learning